More Scottish than British - Carman, Christopher. author. aut Link
IX, 188 p.
Keywords: Using official statistics, this book explores how the SNP managed to confound expectations and win a parliamentary majority in the 2011 Scottish General Election. Perhaps surprisingly, it was not constitutional politics or the return of the Conservatives to power in Westminster but domestic issues that decided the vote in the SNP's favour.